Audio-visual, video and television equipment and systems Part 5. Control, synchronization and address codes Section 2. Method of operation for pulsed cue tone control systems for two still projectors (BSI, 1984)
Audiovisual materials, Teaching aids, Educational equipment, Still-picture projectors, Double, Control systems, Tape recorders, Synchronization, Audio equipment, Audio systems, Audio tapes, Communication equipment, Transparencies, Control tapes, Marking, Frequencies, Time, Magnetic tape recordings, Electronic equipment and components